Ultrasound Anomaly Detection Based on Variational Autoencoders - Milkovic, Fran; Filipovic, Branimir; Subasic, Marko; Petkovic, Tomislav; Loncaric, Sven; Budimir, Marko (2021 12th International Symposium on Image and Signal Processing and Analysis (ISPA), 2021)
Analysis of ultrasonic testing (UT) data is a time-consuming assignment. In order to make it less demanding we propose an approach based on a variational autoencoder (VAE) to filter out the scans without anomalies/defects and in doing so, partially automate the procedure. The implemented approach uses an additional encoder network allowing to encode the reconstructed images. The differences in encodings of input and reconstructed images have shown to be good indicators of anomalous data. Anomaly detection results surpass the results of other VAE based anomaly criteria.